Improving the electrochemical performance of cathode composites using different sized solid electrolytes for all solid-state lithium batteries. Issue 52 (7th October 2021) - Rajagopal, Rajesh; Subramanian, Yuvaraj; Ryu, Kwang-Sun
Abstract : Improving the electrochemical performance of a cathode composite using different sized solid electrolytes for all-solid-state lithium batteries. Abstract : We studied the efficiency of different particle-sized sulfide solid electrolyte-based cathode composites. First, we prepared the Li7 P2 S8 I solid electrolytes with different particle sizes through a high energy ball milling process and solution method. The structural details of the prepared solid electrolytes were studied by powder X-ray diffraction. The surface morphologies and particle size of the electrolytes were studied by field emission electron microscopy. The ionic conductivity of the prepared solid electrolytes was studied by the electrochemical impedance spectroscopy technique. Finally, we have prepared a LiNi0.8 Co0.1 Mn0.1 O2 (NCM 811) based cathode composite and studied the electrochemical performance of the fabricated all-solid-state lithium batteries. The mixed particle-sized solid electrolyte-based cathode composite exhibited higher specific capacitance (127.2 mA h g −1 ) than the uniform-sized solid electrolyte-based cathode composite (117.1 mA h g −1 ). The electrochemical analysis confirmed that the sulfide solid electrolytes with mixed particle size exhibited better electrochemical performance.